Hubungan Dukungan Keluarga Dengan Kualitas Hidup Pasien Pasca-Percutaneous Coronary Intervention (PCI) Di Klinik Jantung RSUD Raden Mattaher Jambi Tahun 2023 - Silvi Salsabila; Nurhusna Nurhusna; Andi Subandi (Pusat Riset dan Inovasi Nasional, 2023)
Heart attacks are caused by a blockage that keeps blood from flowing to the heart and to the brain, resulting in further complications such as failure of the heart muscle to get oxygen supply which results in a person's death. Therefore, patients with heart disease require Percutaneous Coronary Intervention to deal with their treatment. PCI is also known as cardiac angioplasty or percutaneous coronary intervention. PCI installation in patients with heart disease can affect physical activity so that patients really need family support. Family support will increase self-confidence and motivation to face problems and increase the standard of living to improve the patient's quality of life. This type of research uses a quantitative technique with a cross sectional approach. Sampling was carried out by purposive sampling technique with a total sample of 54 people.The results showed that the majority of respondents had good family support, with all dimensions of family support having a good percentage which showed a significant good percentage (100.00%), and had a very good quality of life (75.93%) , with those who have a good quality of life (24.07%). There is a significant relationship between family support and the quality of life of post-percutaneous coronary intervention (PCI) patients in the cardiac clinic room of Raden Mattaher Hospital, Jambi, with the Sig. (2-tailed) is 0.032 less than α (0.05). In addition to the analysis significance value, a correlation coefficient (cc) value of 0.293* was also obtained.The relationship between family support and quality of life of post-percutaneous coronary intervention (PCI) patients in the cardiac clinic room at Raden Mattaher Hospital Jambi in 2023 resulted in a relationship that was sufficient or strong enough and led to a positive relationship, that is, better family support.